SIK : kaderblad Nederlandse Vereniging van Homofielen COC. (Amsterdam : COC, 1970)
Fonds Suzan Daniel (FSD)
Periodiciteit : 10 maal per jaar
Redactie : Frederiksplein 14, Amsterdam
Nederlands
Periodiek